Disease Mongering: social determinants and mental health in the ideological tools that construct and propagate the phenomenon of "manufacturing" mental illnesses - de Oliveira Lima, Aridnaj (Khronos, 2024)
More than ever, the issue of Health is in evidence, and it is not an exclusively medical matter, but it extends to the work of other disciplines and to society as a whole. The global socio-political-economic scenario points to the call, by the World Economic Forum, for "the great reset". The most important countries in the world in a global agenda, dealing with issues such as the environment, education, poverty, hunger, energy, etc., have given great importance to the issue of health. Health is beginning to occupy a place of responsibility not only for the State but for the entire world population on the global stage. In this context, a particular social phenomenon that has already taken root and grown rapidly in many countries, altering discourses about what is health and what is illness, returns to the spotlight: The phenomenon of pathologizing and medicalizing life, in which "non-medical problems are defined and treated as medical problems, usually in terms of diseases or disorders" (Conrad, 1992, p.209), and for every illness a pill that can restore well-being, preferably as quickly as possible. This reality would not be possible without the ideological force of the discourses of three socially significant actors, which operate simultaneously cooperating for the effectiveness of the "manufacture" and propagation of "mental illnesses", namely, the Hegemonic Medical Model, the Diagnostic and Statistical Manual of Mental Disorders (DSM), and the Mass Media as long as they are in the service of pharmaceutical propaganda. This article is a bibliographic review around the social determinants in health/illness processes focusing on mental health, in order to understand the ideological tools that construct and propagate the phenomenon of "manufacturing" mental illnesses.